Christelike etiek in 'n sekulariserende samelewing - Vorster, J.M (AOSIS, 2014)
'Christelike etiek in ΄n sekulariserende samelewing' produces authoritative, fully evidenced and well-reasoned treatment of Christian ethics, a major topic that is of central concern to South Africa's people. It disseminates original research, fosters collaboration of experts and generates new developments within the specific field of Reformed Theology and Christian Ethics.The target audience are specialists in the field of Systematic Theology and contextual ministry. The author applies in Christian ethics the concept of the kingdom of God as the overarching paradigm in order to elucidate societal and ecclesiastical problems which are experienced in morality today. The book's hypothesis is argued and substantiated by using a very wide variety of classic, as well as recent investigations in the field of ethics. What promotes this specific research is the fact that the author not only refers to international researchers, but also to South African theologians and the South African situation. The book further reflects on the phenomenon secularisation and the notion post-secular spirituality, argued against the background of a universal law of nature and a specific scriptural revelation and Christology. In light of the challenges of postmodernity it focuses on the concepts truth, justice and the prophetic calling of the present-day church. The author has managed to translate Christian situation ethics that enriches and stimulates research thoughts, that can assist and advocate reconciliation in South Africa.